Exogenously applied nutrients can improve the chickpea productivity under water stress conditions by modulating the antioxidant enzyme system - Hussain,N. (2022)
Abstract Water stress is one of the major factor restricting the growth and development of chickpea plants by inducing various morphological and physiological changes. Therefore, the present research activity was designed to improve the chickpea productivity under water stress conditions by modulating antioxidant enzyme system. Experimental treatments comprised of two chickpea genotypes i.e. Bhakhar 2011 (drought tolerant) and DUSHT (drought sensitive), two water stress levels i.e. water stress at flowering stage and water stress at flowering + pod formation + grain filling stage including well watered (control) and three exogenous application of nutrients i.e. KCl 200 ppm, MgCl2, 50 ppm and CaCl2, 10 mM including distilled water (control). Results indicated that water stress at various growth stages adversely affects the growth, yield and quality attributes of both chickpea cultivars. Exogenous application of nutrients improved the growth, yield and antioxidant enzyme activities of both chickpea genotypes even under water stress conditions. However, superior results were obtained with foliar spray of potassium chloride on Bhakhar 2011 under well-watered conditions. Similarly, foliar spray of potassium chloride on chickpea cultivar Bhakhar 2011 cultivated under stress at flowering + pod formation + grain filling stage produced significantly higher contents of superoxide dismutase, peroxidase and catalase. These results suggests that the application of potassium chloride mitigates the adverse effects of water stress and enhanced tolerance in chickpea mainly due to higher antioxidant enzymes activity, demonstrating the protective measures of plant cells in stress conditions.